2008
DOI: 10.1111/j.1601-183x.2008.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular responses of the Ts65Dn and Ts1Cje mouse models of Down syndrome to MK‐801

Abstract: Down syndrome (DS), caused by trisomy of human chromosome 21 (chr21), is the most common genetic cause of intellectual disability. The Ts65Dn mouse model of DS is trisomic for orthologs of 94 chr21-encoded, confirmed protein-coding genes and displays a number of behavioral deficits. Recently, Ts65Dn mice were shown to be hypersensitive to the locomotor stimulatory effects of the highaffinity N-methyl-D-aspartate (NMDA) receptor (NMDAR) channel blocker, MK-801. This is consistent with the functions of several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 63 publications
(89 reference statements)
5
50
0
Order By: Relevance
“…Inhibition of CaN activity alters NMDAR gating kinetics (Lieberman and Mody 1994) and causes increased sensitivity to the stimulatory locomotor actions of the NMDAR antagonist MK-801 (Miyakawa et al 2003). The Ts65Dn and Ts1Cje mouse models of DS display similar hypersensitivity to these psychotomimetic actions of MK-801 Siddiqui et al 2008), which supports the hypothesis that CaN is inhibited in these animal models and that, consequently, NMDAR function may indeed be altered. In addition, we also have found that acute doses of the low-affinity uncompetitive NMDAR antagonist memantine rescue learning and memory deficits in Ts65Dn mice in a fearconditioning test ).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Inhibition of CaN activity alters NMDAR gating kinetics (Lieberman and Mody 1994) and causes increased sensitivity to the stimulatory locomotor actions of the NMDAR antagonist MK-801 (Miyakawa et al 2003). The Ts65Dn and Ts1Cje mouse models of DS display similar hypersensitivity to these psychotomimetic actions of MK-801 Siddiqui et al 2008), which supports the hypothesis that CaN is inhibited in these animal models and that, consequently, NMDAR function may indeed be altered. In addition, we also have found that acute doses of the low-affinity uncompetitive NMDAR antagonist memantine rescue learning and memory deficits in Ts65Dn mice in a fearconditioning test ).…”
supporting
confidence: 69%
“…Our research team has found previously that the Ts65Dn mouse displays pharmacological responses consistent with dysfunction in molecular pathways coupled to the gating of NMDARs Siddiqui et al 2008). Proteins encoded by nine genes located on chromosome 21 and in the Ts65Dn trisomic segment (APP, TIAM1, BACH1, SOD1, SYNJ1, ITSN1, RCAN1, DYRK1A, and PCP4) have been shown to interact either directly with NMDARs, or indirectly via the protein phosphatase calcineurin (CaN) (Siddiqui et al 2008;Gardiner 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9). In support of this idea, Ts1Cje are hypersensitive to the channel blocker MK-801 [(ϩ)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine maleate], suggesting dysregulation of NMDAR signaling (Siddiqui et al, 2008). We hypothesize that impairment of NMDA regulation of local dendritic mRNA translation, such as that of DSCAM, may contribute to deficits in dendrite morphology and/or synaptic plasticity in DS.…”
Section: Discussionmentioning
confidence: 69%
“…Altered neurite formation, abnormal dendrite spines (Matsuo et al, 2002;Siddiqui et al, 2008;Tolias et al, 2005;Tolias et al, 2007) SOD1 APP Increase ROS, mitochondrial dysfunction…”
Section: Tiam1 Rac Nmdar Ephbrmentioning
confidence: 99%